ANALISIS KEBUTUHAN SISWA TERHADAP MEDIA PEMBELAJARAN INTERAKTIF PADA MATERI MENJELAJAHI BUMI DAN ANTARIKSA KELAS VI SEKOLAH DASAR - Cahyani, Diva; Uswatun Hasanah; Otib Satibi Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the needs of sixth-grade elementary school students toward interactive learning media on the Earth and Outer Space material. A quantitative descriptive approach was employed, involving 50 students of SDN Periuk 1, Tangerang City, selected through purposive sampling. Data were collected using a Likert-scale questionnaire of 25 items across two variables: students' learning needs (X) and interactive learning media (Y). All 25 items were validated (r count > 0.279; α = 5%) with a Cronbach's Alpha of 0.895, indicating high reliability. Data were analyzed using descriptive percentage analysis (P = f/N × 100%) based on Riduwan (2008). Results showed that Variable X yielded an average of 70.2% (Needed) and Variable Y yielded 71.8% (Needed). The highest score was recorded on item X2, students' enjoyment in learning about Earth and Outer Space phenomena (82.8%, Highly Needed), and item Y6, students' interest in using interactive media for this topic (78.0%, Needed). These findings confirm that students have a significant need for interactive learning media, providing an empirical foundation for the subsequent development of technology-based learning media on this topic.